High Achievers - Susie Kusumayanthi (Universitas Widyatama, 2019)
This paper reports on language learning strategies to develop speaking skill employed by university students categorized as high achiever students. It also focuses on the reasons why they employed those strategies. The study focuses on the above topics because the research concerning language learning strategies to develop speaking skill still receives a little attention in Indonesian EFL context. Some researchers, such as Chamot (1993), affirm that language learning strategy has primarily benefit for developing speaking skill. Two university students were participating in this study. They were studying in the eighth semester at a university in Bandung. They were taking a three-month English for Job Seekers Program supported by the university. In selecting the participants, this study made use of purposeful sampling to gain the important information from the participants (Alwasilah, 2002: 146). The instruments used were questionnaires and interviews. The questionnaires were adapted from Strategy Inventory for Language Learning (SILL) Version7.0 as well as Background Questionnaire developed by Oxford (1990). The interview was an open-ended interview. The study then revealed several findings, among others, is that the high achiever students employed meta-cognitive strategies the most. Concerning the reasons why they employed those strategies were presented in this research.